Digital Philanthropy and Its Role in Building Social Solidarity in Indonesia: A Qualitative Study of Community-Based Social Action - Sugeng Riadi; Anton Bawono; R. Lukma Fauroni (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the role of digital philanthropy in fostering social solidarity in Indonesia through community-based social actions. The rapid growth of digital philanthropic practices in the post-pandemic era, mediated by social media and online platforms, has transformed collective humanitarian engagement. This study aims to explore how digital philanthropy contributes to the formation of social solidarity and social cohesion. A qualitative approach using a case study method was employed. Data were collected through in-depth interviews with fifteen community-based philanthropic actors, participant observation, and social media document analysis. Data analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that digital philanthropy strengthens social solidarity through digital empathy, trust-building, and collective participation. Social media functions as an inclusive interactive space that expands cross-group solidarity networks. However, challenges such as digital inequality and algorithmic bias remain significant. This study concludes that digital philanthropy holds strategic potential to enhance social solidarity when supported by inclusive and sustainable governance frameworks.